(untitled) (Nordic Journal of African Studies, 2003)
The focus of this paper is in formulating a framework where the relationship between such units toponyms, ethnonyms and glossonyms is established in a systematic way. This framework is better presented using Bantu languages in which toponyms, ethnonyms and glossonyms correlate through the same stems.